Electromagnetic background tests for the ILC interaction-point feedback system - Burrows, P; Christian, G; Clarke, C; Constance, B; Khah, H; Hartin, T; Perry, C; Swinson, C; Kalinin, A; Arnold, R; Molloy, S; Smith, S; et al. (2007)
We present results obtained with the T-488 experiment at SLAC Endstation A (ESA). A material model of the ILC extraction-fine design was assembled and installed in ESA. The module includes materials representing the mask, beamline calorimeter, and first extraction quadrupole, encompassing a stripline interaction-point feedback system beam position monitor (BPM). The SLAC high-energy electron beam was used to irradiate the module in order to mimic the electromagnetic (EM) backgrounds expected in the ILC interaction region. The impact upon the performance of the feedback BPM was measured, and compared with detailed simulations of its expected response.